2003
DOI: 10.1007/s00109-003-0448-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of the glutathione S-transferase genes and cigarette smoking on occurrence and severity of coronary artery risk

Abstract: Cardiovascular diseases and cancer are the main causes of death in developed countries. Mortality trends for these diseases suggest that they share common pathogenetic mechanisms. Glutathione S-transferase (GST) is a family of enzymes that detoxify reactive electrophiles, particularly present in tobacco smoke. Glutathione S-transferase null M1 and T1 (GSTM1 and GSTT1) genotypes have often been associated with increased risk of developing cancer. Our hypothesis was that the polymorphic GSTM1 and GSTT1 genes mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 33 publications
2
41
2
2
Order By: Relevance
“…The association between the GST genotype and lung cancer is less clear, because both positive and negative data have been reported (34,38). Similarly, in some studies, the GSTM-null phenotype was associated with an increase in coronary artery disease in smokers (33), whereas in others the null phenotype has been reported to be associated with a decrease in risk of myocardial infarction in smokers (46). Although GSTM participates in the metabolism of several PAHs present in CS, many of the small reactive carbonyls present in CS, such as acrolein and crotonaldehyde, are preferentially conjugated by GSTP (8).…”
mentioning
confidence: 93%
“…The association between the GST genotype and lung cancer is less clear, because both positive and negative data have been reported (34,38). Similarly, in some studies, the GSTM-null phenotype was associated with an increase in coronary artery disease in smokers (33), whereas in others the null phenotype has been reported to be associated with a decrease in risk of myocardial infarction in smokers (46). Although GSTM participates in the metabolism of several PAHs present in CS, many of the small reactive carbonyls present in CS, such as acrolein and crotonaldehyde, are preferentially conjugated by GSTP (8).…”
mentioning
confidence: 93%
“…It has been demonstrated that individuals carrying the null GSTM1 allele are more susceptible to inflammatory pathologies and at increased risk of some smoking-related cancers. Smokers that lack the GSTM1 gene develop both CHD and atherosclerosis at higher rates (Salama et al, 2002;Masetti et al, 2003). Conversely, this hypothesis has been rejected in other studies, in which the null GSTM1 genotype has been associated with lower risk of myocardial infarction and peripheral vascular disease (Wilson et al, , 2003.…”
Section: Discussionmentioning
confidence: 98%
“…Pemble et al (1994) reported that approximately 20% of the white population is homozygous for a null variant of GSTT1, which is consistent with our findings (17.3 to 28.3%). The role of GSTT1 in deactivating the epoxides in cigarette smoke, together with its absence in smoking-related cancers, suggests that individuals homozygous for the null allele may be at higher risk of cancer (Salama et al, 2002;Masetti et al, 2003). However, other studies suggest that the absence of this gene is associated with a lower risk of damage and disease (Li et al, 2000;Olshan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high heterogeneity, 3 articles [58][59][60] were excluded from the analysis, after which the heterogeneity decreased significantly to 41% (p = 0.1) for the remaining studies. However, the effect of the GSTM1 genotype on the micronucleus frequency was still evident, with a SMD = -0.33 (95% CI: -0.5-(-0.17), p < 0.0001) (Table 10).…”
Section: Effect Of the Gstm1 Genotype On The Micronucleus Frequencymentioning
confidence: 99%